Real-resumes for restaurant, food service & hotel jobs-- : including real resumes used to change careers and transfer skills to other industries / [Editor] Anne McKinney - McKinney, Anne, 1948-editor
Provides advice on looking for jobs in the field of restaurant, food service, and hotel management, and provides hundreds of sample cover letters and resumes.